A Visual-Based Pick and Place on 6 DoF Robot Manipulator - Wijaya, Ryan Satria; Pratama, Adhitya; Fatekha, Rifqi Amalya; Soebhakti, Hendawan; Prayoga, Senanjung (Journal of Applied Electrical Engineering, 2024)
This paper discusses the application of visual servoing on a 6 DOF robotic manipulator for industrial automation. With visual feedback, the manipulator can perform pick and place operations accurately and efficiently. We explore feature- and model-based visual servoing methods and object detection techniques, including deep learning algorithms. The experimental results show that the integration of visual servoing with pick and place method as well as object detection improves the performance of manipulators in industry. This research contributes to the understanding of visual servoing technology in industrial automation. The conclusion shows that the manipulator is more precise in controlling the X-axis shift in the first two experiments, but faces challenges in the third experiment. The success of the system is affected by environmental factors such as lighting. For further development, research is recommended to improve robustness to environmental variations as well as evaluation of execution speed and object positioning accuracy.